Deliberation and Legitimacy in Transnational Governance: The Case of Environmental Impact Assessments - Craik, Neil (Victoria University of Wellington Law Review, 2007)
This paper begins by recognising that transnational environmental governance structures have been the subject of criticism as lacking democratic legitimacy. The author suggests, however, that instead of using the traditional liberal view of democracy where decisions are made by majority agreement, deliberative democracy may provide a solution. This approach focuses not on the aggregation of fixed interests within a given territory but on a continual process of dialogue between decisionmakers and all those affected, a process of mutual justification by the exchange of reasons. The author examines the possible application of this theory, using environmental impact assessments carried out pursuant to environmental conventions as an example of the theory in practice. The author shows how a deliberative democratic approach brings a range of advantages to decisionmaking concerning crossborder environmental harm, concluding that this approach has the potential to enhance the legitimacy of environmental decisionmaking beyond the state.